Comparison of molecular genetic methods of detection of mutations in the CALR gene in myeloproliferative disorders - L. A. Kesaeva; A. Yu. Bulanov; Yu. P. Finashutina; V. V. Tikhonova; O. N. Solopova; E. N. Misyurina; N. N. Kasatkina; N. A. Lyzhko; V. A. Misyurin; A. A. Turba; A. A. Solodovnik; I. N. Soldatova; et al. (Успехи молекулярной онкологии, 2019)
Molecular genetic detection of CALR gene somatic mutations is required for myeloproliferative neoplasms diagnosis and treatment according to the novel WHO clinical recommendations. CALR mutations are found in approximately 25–35 % cases of essential thrombocythemia and primary myelofibrosis and they are associated with benign clinical outcome. In this study we have compared sensitivity and selectivity of seve ral different options of CALR mutation molecular genetic detection in blood samples of 379 CMD patients and 17 healthy donors. Among methods compared in our study there have been conventional polymerase chain reaction with electrophoretic detection, real-time quantitative polymerase chain reaction, direct Sanger sequencing of polymerase chain reaction fragments and polymerase chain reaction high resolution melting curve analysis. By means of melting curve analysis CALR mutations have been found in 97 (25.5 %) patients, whereas in the cases of Sanger sequencing and polymerase chain reaction there have been 87 (23.0 %) and 84 (22.1 %) CALR mutation positive patients respectively.